2015
DOI: 10.1155/2015/235195
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Precursor Cells in Spinal Cord Injury: A Review and Update

Abstract: Spinal cord injury (SCI) is a devastating condition to individuals, families, and society. Oligodendrocyte loss and demyelination contribute as major pathological processes of secondary damages after injury. Oligodendrocyte precursor cells (OPCs), a subpopulation that accounts for 5 to 8% of cells within the central nervous system, are potential sources of oligodendrocyte replacement after SCI. OPCs react rapidly to injuries, proliferate at a high rate, and can differentiate into myelinating oligodendrocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 223 publications
(238 reference statements)
0
50
0
Order By: Relevance
“…Tgfb1 upregulation in transplanted mouse neural cells in injured CNS has been reported to reflect a response to inflammatory activity, and both Bcl2 and Notch increase NSC survival (Capone et al., 2007, Kumamaru et al., 2012, Koch et al., 2013). In parallel, observed changes in BMP2, NOTCH, OLIG2, FGF2, ASCL1, DLL1 , and PAX6 are consistent with previous reports of modulation of NSC differentiation and lineage selection (Zhou and Anderson, 2002, Wu et al., 2003, Cheng et al., 2007, Sugimori et al., 2007, Kumamaru et al., 2012, Koch et al., 2013, Vasconcelos and Castro, 2014, Li and Leung, 2015). For the neurite outgrowth and migration category, upregulation of genes such as DCX (Schaar et al., 2004),  NRP2 (Schwarz and Ruhrberg, 2010), and EFNB1 (Tanaka et al., 2004) suggest increases in neuronal migration, axonal outgrowth, and guidance signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Tgfb1 upregulation in transplanted mouse neural cells in injured CNS has been reported to reflect a response to inflammatory activity, and both Bcl2 and Notch increase NSC survival (Capone et al., 2007, Kumamaru et al., 2012, Koch et al., 2013). In parallel, observed changes in BMP2, NOTCH, OLIG2, FGF2, ASCL1, DLL1 , and PAX6 are consistent with previous reports of modulation of NSC differentiation and lineage selection (Zhou and Anderson, 2002, Wu et al., 2003, Cheng et al., 2007, Sugimori et al., 2007, Kumamaru et al., 2012, Koch et al., 2013, Vasconcelos and Castro, 2014, Li and Leung, 2015). For the neurite outgrowth and migration category, upregulation of genes such as DCX (Schaar et al., 2004),  NRP2 (Schwarz and Ruhrberg, 2010), and EFNB1 (Tanaka et al., 2004) suggest increases in neuronal migration, axonal outgrowth, and guidance signaling.…”
Section: Discussionmentioning
confidence: 99%
“…OLGs are thought to be susceptible to the toxicity of the acute lesion environment after SCI as they undergo both necrosis and apoptosis in the acute phase while apoptosis may be prevalent in chronic phases of the injury [28, 29]. Loss of OLGs causes demyelination and impairs axon function and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of OLGs causes demyelination and impairs axon function and survival. Oligodendrocyte precursor cells (OPCs) are potential sources for replacement of OLGs after SCI [29]. It is believed that OPCs act rapidly following injuries, proliferate at a high rate, and can differentiate into myelinating OLGs.…”
Section: Introductionmentioning
confidence: 99%
“…They respond quickly after injury and proliferate fast, which makes them a potential source of oligodendrocyte replacement after SCI. Although effective oligodendrocyte replacement and adequate remyelination can significantly improve neurological function, endogenous remyelination is very difficult after trauma because of the adverse microenvironment and inflammatory changes after SCI [27,28]. A clinical trial of patients with complete thoracic SCI has shown that transplantation of human embryonic stem cell-derived oligodendrocyte progenitor cell therapy product does not cause any adverse clinical observations, toxicity, allodynia or tumors, which suggests that OPC is also a good candidate [29].…”
Section: Oligodendrocyte Precursor Cells (Opcs)mentioning
confidence: 99%